2021
DOI: 10.3991/ijoe.v17i05.20991
|View full text |Cite
|
Sign up to set email alerts
|

Non-Traditional Labs and Lab Network Initiatives: A Review

Abstract: Lab-based education has always played an important role in teaching students. Making remote and virtual labs communicate with one another by creating networks of labs can enhance the traditional way of learning as well as reduce the costs of implementing and using labs. This paper provides a review of the literature on non-traditional labs and lab network initiatives up to 2020. With the term ‘non-traditional labs’, we mean virtual, remote and hybrid labs, whereas with the term ‘lab network’, we indicate a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…What is missing is a deep analysis of financial and organisational aspects for making labs and networks in which they are inserted robust from a life cycle perspective (Esposito, Kammerlohr, et al, 2021). In this regard, Esposito, Mezzogori, et al (2021) have showed that most digital online experiences last only for the time in which they are funded by institutions and organizations under the programs of national or international projects. From this point of view, Esposito, Kammerlohr, et al (2021) analyzed the possibility of using research data for business part nerships upon payment, with generally positive results from several Italian companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What is missing is a deep analysis of financial and organisational aspects for making labs and networks in which they are inserted robust from a life cycle perspective (Esposito, Kammerlohr, et al, 2021). In this regard, Esposito, Mezzogori, et al (2021) have showed that most digital online experiences last only for the time in which they are funded by institutions and organizations under the programs of national or international projects. From this point of view, Esposito, Kammerlohr, et al (2021) analyzed the possibility of using research data for business part nerships upon payment, with generally positive results from several Italian companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SGs in engineering education are not a recent topic: SG have already been proposed and implemented in engineering education more than 50 years ago [3], [4], although they have not always been taken very seriously, especially in the first years [5]. More recently, thanks to the rise of non-traditional labs and lab networks [6], [7], and to the improvements in distance learning and online services for education [8], SGs have seen a new wave of interest as they are more and more perceived as immersive and entertaining learning tools [9]. This reconsideration is also accelerated by the fact that many teachers consider learning by doing as an effective teaching style to close the gap between theory and practice [10], and SGs give learners the opportunity to explore and understand a simulated context by reflecting everyday practical processes, without exposing learners to most the risks that these processes include [11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this fact, the development and use of laboratories has increased significantly in recent years [3]. In particular, [4] showed that Non-Traditional Labs (NTLs), i.e., laboratories which differ from traditional hands-on ones, and Lab Network Initiatives (LNIs), i.e., an environment that combines at least two isolated online laboratories connected to each other, have become more and more common in the last two decades ([3]- [5]). These labs can mostly be accessed via web, and they might offer the possibility to perform both virtual and real experiments, by means of remote use enabled by sensors, actuators, controllers, and smart devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the rising importance of laboratories in STEM, IIoT and I4.0, [4] highlighted that the duration of the before mentioned labs is highly depending on project fundings. This information strengthens the need to hoard funds to keep the laboratories active and up to date.…”
Section: Introductionmentioning
confidence: 99%